Peran Katekese Dalam meningkatkan Iman dan Keterlibatan Umat di Gereja Paroki Santo Petrus Pariti Sulamu - Yohanes Rusae; Bonefantura Jemy Bria (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
Background: Catechesis is an integral part of the Catholic Church's evangelization mission, aiming to foster, deepen, and mature the faith of the congregation. At the St. Petrus Pariti Sulamu Parish Church, catechesis is one of the primary pastoral programs in forming an active and engaged community of believers. Objective: This study aims to analyze the role of catechesis in enhancing the faith and engagement of the congregation at the St. Petrus Pariti Sulamu Parish Church, and to identify factors influencing the effectiveness of the catechesis program. Method: This study used a qualitative approach with descriptive methods. Data were collected through participant observation, in-depth interviews with the parish priest, catechists, and congregation, and analysis of parish pastoral documents. Results: : Research shows that catechesis plays a significant role in enhancing the understanding of faith, spirituality, and active participation of the congregation in church life. Structured and contextualized catechesis programs contribute to the formation of a solid Christian community. Conclusion: Effective catechesis requires a holistic approach, involving all components of the parish, and adapted to the local socio-cultural context.